Interval training for cycling. From lab to races - Rønnestad, B.; Tur, C.; Ahumada, F. (Sportraining, 2024)
Interval Training for Cycling is a reference for coaches and cyclists that want to improve their training methods and tools to apply every day. With 1077 references to the scientific literature, the authors present solid foundations of the acute and chronic responses of the human body to the training in the heavy and severe intensity domains. The book focuses on: " Describe and explain the most important concepts related to training and exercise physiology like VO2max, critical power, functional threshold power, maximal lactate steady state, ventilatory thresholds, record power profile, mean maximal values, and other important training metrics. " Study the training adaptations to the moderate, heavy, and severe intensity domain. " Study the physiological and performance profile as well as lab and field tests of mountain bike and road cyclists. " Study the most important findings of the scientific literature related to interval training (Sprint Interval Training, Long Intervals, Multiple Short Intervals and Threshold Intervals). " Study the sport nutrition guidelines to optimize interval training. " Study the training periodization, performance peaking and tapering strategies to optimize performance. " Present the training philosophy and training approach of super elite road and mountain bike cyclists. This is the most comprehensive and better supported book related to cycling interval training that has been written and will help coaches and cyclists to achieve their goals.